Strengthening Islamic Religious Education Teacher Competencies in the Society 5.0 Era: Challenges and Interventions - Nasikin, Muhammad; Abzar, Muhammad; Afandi, Nur Kholik (AL-ISHLAH: Jurnal Pendidikan, 2024)
The Society 5.0 era brings significant changes to various aspects of life, including education. Islamic Religious Education (PAI) teachers play a vital role in shaping students' character, ensuring they can control technology's negative influences and use it positively. This study aims to identify the challenges faced by PAI teachers in the Society 5.0 era and evaluate the strengthening of their competencies through the PAI Subject Teachers' Deliberation (MGMP) in Kutai Kartanegara, focusing on artificial intelligence (AI) integration. A qualitative case study approach was employed, with goal-setting theory guiding the intervention in a teacher training program. Data were collected through in-depth interviews with PAI teachers, participatory observation, and analysis of teaching materials produced during the training. The intervention involved AI-based applications like Google Docs' AI writing assistant for lesson planning and AI-driven tools for evaluating student performance. Thematic analysis was used to identify key patterns and themes regarding the challenges and opportunities in strengthening teacher competencies. The results showed that AI training improved the effectiveness and efficiency of teaching materials, marked by more interactive content, shorter preparation times, and better alignment with student needs. Additionally, there was a significant increase in student engagement during lessons, highlighting the success of AI technology in enhancing the learning process.